A inserção da educação ambiental no currículo do curso de Agronomia: um estudo de caso na UFSM. - Souza, Sandra Elisa Réquia (2006)
This study has as research object the environmental education inserting in Agronomy Course curriculum of Universidade Federal de Santa Maria, having as motivations: the work developed with the team of Pedagogical Support Unit of Rural Sciences Center, that objectives to help the Principal in Center s subjects didactical and pedagogical matters; the personal effort to bring to Course the humanistics, socials and environmental aspects to aid the construction of rural sustainability. The research have two moments: one, when was observed and analysed the scene of elaboration of new Political and Pedagogical Project of Course in respect to possibilities and difficulties to insert environmental education with interventions in various moments, searching create spaces of dialog and reflection to innovate in this sense. In other moment, are used the semi- structured interview instrument to analyses speeches of teachers and students that actively participates of such process and to understand of yours conceptions of environmental education, sustainability and environment, to verification how interferes in the new Course project. For this, are realised a qualitative investigation, with a critical and dialectical approach and the results obtained permits observes that still exists epistemological, pedagogical and political obstacles to inserts emancipator environmental education, such as: no make a new direction to research, the fragmented and hierarchyzed curriculum. With dissociation between theory and practice, traditional pedagogical practice with predominance the oral exposition methodology and classificatory learning evaluation. Instead this bareers, the Course presents potential to work, translated in innovations to build a professional education that contemplates humanistic, social and environmental aspects. Such, a professional profile more coherent with society s demands, a more flexible curriculum than the ancient, introduction of a assignment that integrates matters of four initial periods of Course, existence and permanency of groups that inquires of hegemonic mainstream of Agronomy Course.